Examining Perceived Organizational Support and Teacher Empowerment - Muttaqin, Imron (Letiges, 2023)
This study aimed to investigate influence of perceived organizational support (POS) and teacher empowerment on teacher organizational commitment with job satisfaction as mediating construct. Study conducted on Institut Agama Islam Negeri (IAIN) Pontianak, west Borneo, Indonesia. Participant are teacher student on professional education and training program/Pendidikan Profesi Guru (PPG) at Institut Agama Islam Negeri Pontianak. Questionnaire used for collecting data. Findings reveal that the influence of perceived organizational suport (POS) on organizational commitment (OC) are not signifikan, but became positive significant while job satisfaction as mediating variable. perceived organizational suport (POS) positively predict job satisfaction. Islamic educational institutions are advised to increase teacher job satisfaction, because it relates to their organizational commitment to educational institutions.